Targeting Tax Relief at Youth Employment - Matthew D. Webb; Casey Warman; Arthur Sweetman (Institute for the Study of Labor (IZA), 2016)
Canada's Youth Hires program was a targeted employment subsidy that rebated employment insurance premiums to employers with net increases in insurable earnings for youth aged 18-24. Using a difference-in-differences approach, in each of two datasets statistically and economically significant employment impacts are observed. Most of the evidence suggests that the 2-2.4 weeks of increased employment resulted from an aggregate reduction in those not in the labour force, with at most a modest change in the unemployment rate. Many estimated effects are larger for males than females. Notably, strong evidence of displacement (substitution away from slightly older non-subsidized workers) is not observed. However, there may be a small reduction in full-time schooling for the targeted group.
Keywords: J23; J65; J68; 330; youth unemployment; displacement; unemployment insurance; unemployment; targeted tax policy